Evaluasi Program Dana Bergulir Samisake Di Kota Bengkulu (Studi di Kelurahan Sawah Lebar) - Mandala Putra, Bobby; Rama Krisyanto; Harmiati (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2024)
The aim of this research is to evaluate the effect of the Samisakerolling program on increasing income, welfare and employment opportunities inSawah Lebar Village, Bengkulu City. The research was conducted in SawahLebar Village, Bengkulu, from April 10 to May 10 2023. The approach usedwas a qualitative method with a narrative strategy. This research refers to theobjectives of the Samisake revolving fund program as regulated in BengkuluCity Regional Regulation No. 12 of 2013 concerning Management of SamisakeRevolving Funds, which includes increasing community income and welfare,expanding employment and business opportunities through the creation of newjobs, as well as implementing acceleration efforts. strengthening the people'seconomy through the involvement of the City Government, business world,local communities and community groups in participatory processes. However,due to limited time, resources and budget, the research focus is only on twoobjectives, namely increasing people's income, improving people's welfare andexpanding employment opportunities. The research results show that theSamisake Revolving Fund Program has succeeded in increasing recipients'income and welfare as well as opening up new job opportunities. This programsucceeded in increasing the gross and net income of the recipients. As manyas 73.33% of informants who were recipients of the Samisake program felt apositive impact after receiving the program. This positive impact includeschanges in conditions in terms of education, health and housing for Samisakeprogram recipients. As many as 33.33% of recipients of this programsucceeded in increasing their workforce to increase their business productivity